Case report: A case of mast cell leukemia treated with avapritinib: from diagnostic challenge to transplantation - Faraci, Danilo Giuseppe; Caravelli, Daniela; Schianca, Fabrizio Carnevale; Zaniol, Elena; Enrico, Fiorenza; Boffano, Carlo; Labate, Carmelo; Sterpi, Greta; Fornari, Alessandro; Sangiorgio, Valentina; Crisà, Elena (Frontiers in Oncology, 2026)
Systemic mastocytosis (SM) is a rare hematological neoplasm characterized by the proliferation and accumulation of clonal mast cells (MCs) in the skin, bone marrow, and other extracutaneous organs. Mast cell leukemia (MCL) is the rarest and more aggressive subtype of SM, with very poor prognosis and abysmal survival. Treatment strategies are poorly defined and non-standardized, ranging from symptomatic management to KIT-targeted tyrosine kinase inhibitors and, in selected cases, allogeneic stem cell transplantation, currently the only potentially curative chance for MCL patients. Here, we report a case of a 66-year-old woman affected by MCL, highlighting clinical features, diagnostic challenges and complexity, and our treatment choices. Furthermore, we review current literature data and emerging therapeutic approaches, emphasizing the importance of greater clinical awareness and comprehensive multidisciplinary approach to correctly diagnose and treat this condition in order to improve patient outcomes in this challenging disease.